2015
DOI: 10.5604/12321966.1185760
|View full text |Cite
|
Sign up to set email alerts
|

Head pediculosis in schoolchildren in the eastern region of the European Union

Abstract: Objective. The aim of the study was to investigate the prevalence of head pediculosis among children from state primary schools in the villages and towns in eastern Poland, one of the poorest regions of the European Union. Materials and methods. The study was conducted in 2009-2012 in 30 rural and urban State schools. Current and previous results (1996-2000) of examinations performed in the study area were compared. The impact of socioeconomic factors on the prevalence of head pediculosis in eastern Poland i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 13 publications
1
23
0
1
Order By: Relevance
“…The prevalence of pediculosis capitis in this study was 68.7% of children in primary schools infested with head lice. This prevalence is quite high compared to studies reported recently in several places, 2.01% in the European Union [26], 12.2% in Riyadh, Saudi Arabia [21], 10% in Barat Daya Iran [25] and 44% in Batambang, Cambodia [27]. Respondents from the researches mentioned previouslty were generally elementary school children in urban areas, where as this research was conducted in rural areas.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The prevalence of pediculosis capitis in this study was 68.7% of children in primary schools infested with head lice. This prevalence is quite high compared to studies reported recently in several places, 2.01% in the European Union [26], 12.2% in Riyadh, Saudi Arabia [21], 10% in Barat Daya Iran [25] and 44% in Batambang, Cambodia [27]. Respondents from the researches mentioned previouslty were generally elementary school children in urban areas, where as this research was conducted in rural areas.…”
Section: Discussionmentioning
confidence: 53%
“…In rural areas, pediculosis capitis was reported to be higher by a number of earlier studies [26]. Megrin [21] had point out that area of residence contributes significantly to the rate of head lice infestation in children (19,2%, p < 0.001).…”
Section: Fig-1: Kawiley Vilage (Rignolda Djamaluddin)mentioning
confidence: 90%
“…The highest pediculosis incidence rate was observed in developing countries of Central America, Asia, and Africa [2], [3], [4], [5], [6], [7]. However, the growth of population infestation with pediculosis, primarily head pediculosis, has also been noted in prosperous socioeconomic countries: the UK, Norway, the USA, and others [8], [9], [10], [11]. In Russia, up to 300 thousand cases of pediculosis are registered every year.…”
Section: Introductionmentioning
confidence: 99%
“…[2]. At its peak, the disease will be of a far greater prevalence, where the widespread prevalence rate is reported up to 80% in different parts of the world which increases progressively [3][4][5].…”
Section: Introductionmentioning
confidence: 99%